2021
DOI: 10.3390/ijgi10050327
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Political Determinants of Ecological Vulnerability in the Qinghai–Tibet Plateau: A Case Study of Shannan, China

Abstract: Changing land-use patterns in the Qinghai–Tibet Plateau (QTP) due to natural factors and human interference have led to higher ecological vulnerability and even more underlying issues related to time and space in this alpine area. Ecological vulnerability assessment provides not only a solution to surface-feature-related problems but also insight into sustainable eco-environmental planning and resource management as a response to potential climate changes if driving factors are known. In this study, the ecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…With the expansion of urbanization, there is also a risk of spillover of ecological and environmental stresses, especially the trend of expansion to agricultural and pastoral development areas. In the environmental evaluation results, the peripheral areas of these urban agglomerations show different degrees of pollution, and this finding is consistent with many previous studies [62][63][64].…”
Section: Discussionsupporting
confidence: 92%
“…With the expansion of urbanization, there is also a risk of spillover of ecological and environmental stresses, especially the trend of expansion to agricultural and pastoral development areas. In the environmental evaluation results, the peripheral areas of these urban agglomerations show different degrees of pollution, and this finding is consistent with many previous studies [62][63][64].…”
Section: Discussionsupporting
confidence: 92%
“…Remarkably, this pattern did not fit every prefecture. In Shannan, the correlation between urbanization and EVI was negative during 1990-2015 [82], which meant that though EVI in Tibet overall was influenced by urbanization, the situation was spatially heterogeneous.…”
Section: Driving Factors Of Ecological Vulnerabilitymentioning
confidence: 99%
“…Built-up land is mainly distributed at the second and third TGs, which is more suitable for human living with enough water along a river and increases with time. According to previous studies, ecological protection policy such as an artificial afforestation program and a sloping land conversion program in Shannan has achieved certain results [ 30 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers initially revealed that rapid urbanization causes a continuous decline in regional ESV [ 28 , 29 ]. Different from the developed, urbanized areas, the impacts of urbanization on the Qinghai–Tibet Plateau with suffering serious environmental deterioration from both climate change and human interventions, attract less attention [ 30 , 31 ]. There are obvious differences in the distribution of land vegetation patterns and the responses of ESV to urbanization in different terrain conditions [ 32 ].…”
Section: Introductionmentioning
confidence: 99%